The Dialectic of Use Value and Exchange and Direction of Percipient and Purposeful Human Action in Mario Ferreira dos Santos - Veras, Murilo Carlos Muniz (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2017)
The perception of knowledge and the unity of will and human action have amazed philosophers and scientists. Mario Santos proposes that the perception and the expression of social and economic reality in the concrete existence of the beings depend on understandings of conceptual antinomies, schematic logics and ontico-ontologicals that are dialectically complementary. In economics, the theme "value", the antinomy between use and exchange values, and posterior developments in several other categorical fields should allow outlining intentional directions of human actions in different scenarios, as well as the propension to consume and the configuration of the exchange market’s structure. We also propose a development of dialectics to support value motivations of economic agents.